Visible‐Light Promoted C–O Bond Formation with an Integrated Carbon Nitride–Nickel Heterogeneous Photocatalyst - Vijeta, Arjun (Angew Chem Int Ed Engl, 2021)
Ni‐deposited mesoporous graphitic carbon nitride (Ni‐mpg‐CN(x)) is introduced as an inexpensive, robust, easily synthesizable and recyclable material that functions as an integrated dual photocatalytic system. This material overcomes the need of expensive photosensitizers, organic ligands and additives as well as limitations of catalyst deactivation in the existing photo/Ni dual catalytic cross‐coupling reactions. The dual catalytic Ni‐mpg‐CN(x) is demonstrated for C–O coupling between aryl halides and aliphatic alcohols under mild condition. The reaction affords the ether product in good‐to‐excellent yields (60–92 %) with broad substrate scope, including heteroaryl and aryl halides bearing electron‐withdrawing, ‐donating and neutral groups. The heterogeneous Ni‐mpg‐CN(x) can be easily recovered from the reaction mixture and reused over multiple cycles without loss of activity. The findings highlight exciting opportunities for dual catalysis promoted by a fully heterogeneous system.